If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -5x = 11 + -1(6x + 3) Reorder the terms: 9 + -5x = 11 + -1(3 + 6x) 9 + -5x = 11 + (3 * -1 + 6x * -1) 9 + -5x = 11 + (-3 + -6x) Combine like terms: 11 + -3 = 8 9 + -5x = 8 + -6x Solving 9 + -5x = 8 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + -5x + 6x = 8 + -6x + 6x Combine like terms: -5x + 6x = 1x 9 + 1x = 8 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + 1x = 8 + 0 9 + 1x = 8 Add '-9' to each side of the equation. 9 + -9 + 1x = 8 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 8 + -9 1x = 8 + -9 Combine like terms: 8 + -9 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 5x+2+2x+6=67 | | M-8-6m=-50+m | | -6x+3x+20-10x= | | 3x^2=43x+136 | | 4y^2+7y-3=0 | | .7x-.1=.5-.5(3-2x) | | -36y^2+12y+6=0 | | -3x-(-6)=12 | | (5+6i)+(2+4i)= | | 12x-3=7x-2 | | m+3m-5m+3= | | 5k-3.5-4.3k-3.3k+4= | | 0.05x+0.08(200-x)=14.5 | | 4x+7-6(x+1)=7X+6 | | 9-(5-8x)=4x+2 | | 3x+0.5y+10z=100 | | 11x+5-8x=8(x+1)+12 | | g(x)=5x | | 9z^2+35z+13=8z^2+45z-8 | | -2r+1.8-4.7r-2.5r+4= | | 5=-2-b | | 3-3a=8-2(2a+7) | | .3b=.9 | | 4a^2=32 | | N+2=2n-5 | | 4-5(a+3)= | | 1/4(7+3n)=-n/8 | | log(3)9-log(5)625+log(7)343=equation | | (x-2)3+7=6(2x-4)+7 | | 300=(x+5-4)(x-4)(2) | | -4z+4.6-2.5z-0.1+1= | | 6w=2m+1 |